A Multiple Fixed Point Result for θ, ϕ, ψ-Type Contractions in the Partially Ordered s-Distance Spaces with an Application. (6th January 2022) - Rashid, Maliha; Kalsoom, Amna; Ghaffar, Abdul; Inc, Mustafa; Sene, Ndolane
Abstract : In this manuscript, the aim is to prove a multiple fixed point (FP) result for partially ordered s -distance spaces under θ, ϕ, ψ -type weak contractive condition. The result will generalize some well-known results in literature such as coupled FP (Guo and Lakshmikantham, 1987), triple fixed point (Berinde and Borcut, 2011), and quadruple FP results (Karapinar, 2011). Moreover, to validate the result, an application for the existence of solution of a system of integral equations is also provided.